Quality Of Marriage Registration Services Through The Marriage Management Information System (SIMKAH) Application At The Religious Affairs Office (KUA) Tanete Riaja, Barru Regency - A. Z., Wahyul; Masyitah, Masyitah (SEAN Institute, 2024)
This study aims to find out how the quality of marriage registration services through the simkah application at the religious affairs office (KUA) of Tanete Riaja District, Barru Regency. In addition, this study also aims to find out what factors affect the quality of marriage registration services through the simkah application at the religious affairs office (KUA) of Tanete Riaja District, Barru Regency. The type of research used is the qualitative type. Data collection techniques were obtained through interviews, observations and documentation. Data analysis techniques are data reduction, data presentation and conclusion making. The results of this study show that the quality of marriage registration services through applications (simkah) at the Religious Affairs Office (KUA) Tanete Riaja Barru Regency. It can be said that it is good, but there are still some shortcomings. However, in carrying out marriage services, the staff at KUA Tanete Riaja District, Barru Regency is still of high quality. With this SIMKAH, all service process data will be fast and effective. The factors that affect the quality of marriage registration services through the simkah application at the religious affairs office (KUA) of Tanete Riaja District, Barru Regency are the internet network, but the Religious Affairs Office of Tanete Riaja District has installed a network.